2019
DOI: 10.3390/ani9100743
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Testicular Histopathology of Mice Exposed to Restraint Stress

Abstract: Simple SummaryThe search for effective medicines is challenging. Resveratrol is a phytoalexin, and its function remains unelucidated. Therefore, we undertook the present study to investigate reproductive disturbances due to restraint stress in mice and whether resveratrol plays an anti-stress role. Our results confirmed that resveratrol plays a potential role in the reduction of stress in mice. AbstractWe evaluated immobilization stress and resveratrol supplementation in immature male mice at 30 days of age fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
3
14
0
Order By: Relevance
“…The decrease in germ cell number was due to downregulation of testosterone levels. These results are consistent with our previous findings [29]. This study demonstrates that MOTILIPERM restores seminiferous tubular structure, protects germ cell proliferation, and improves sperm count and sperm motility.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The decrease in germ cell number was due to downregulation of testosterone levels. These results are consistent with our previous findings [29]. This study demonstrates that MOTILIPERM restores seminiferous tubular structure, protects germ cell proliferation, and improves sperm count and sperm motility.…”
Section: Discussionsupporting
confidence: 94%
“…The present investigation also showed that testicular apoptosis is significantly increased in stressed rats, which is consistent with previous findings [1,3,11,15,29,45]. Bax is an important pro-apoptotic gene; Bcl-2 is an anti-apoptotic gene; and cleaved caspase-3 is an executioner caspase that is essential for triggering apoptosis [24].…”
Section: Discussionsupporting
confidence: 93%
“…2) (A = 3.14 √ 2) [33]. In order to compare histopathological parameters and MRS values, one-way analysis of variance [37] results for multiple comparison tests by Dennett's multiple comparisons (which compares the mean of each column with the mean of control column) were carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (Sigma Chemical Co., St Louis, MO, USA) was diluted to 5% in the vehicle (CMC, sodium carboxymethyl cellulose) [33,34]. The Beijing Institute for Pharmacology and Toxicology (China) supplied sodium carboxymethyl cellulose with trans-resveratrol for oral gavage at 0.5% in CMC.…”
Section: Drugsmentioning
confidence: 99%
“…Our findings illustrated that luminal diameter, luminal area, Leydig cell area, and width of tunica albuginea increased as yaks aged toward sexual maturity. Sheeraz et al [46] evaluated luminal diameter (69.10 ± 16.99 µm 2 ), luminal area (49.26 ± 8.47 µm 2 ), Leydig cell area (108.19 ± 30.60 µm 2 ), and width of tunica albuginea (12.99 ± 1.35 µm) in mice. In our findings, the mean cross-sectional area of the seminiferous tubules varied from 46,675.0 ± 2689 to 50,812 ± 3711 µm 2 for different ages of yak, and the differences were not significantly different.…”
Section: Discussionmentioning
confidence: 99%